Nocturnal enteral nutrition is therapeutic for growth failure in Fanconi‐Bickel syndrome - Pennisi, Alessandra; Maranda, Bruno; Benoist, Jean‐François; Baudouin, Véronique; Rigal, Odile; Pichard, Samia; Santer, René; Romana Lepri, Francesca; Novelli, Antonio; Ogier de Baulny, Hélène; Dionisi‐Vici, Carlo; Schiff, Manuel (Journal of inherited metabolic disease, 2020)
Fanconi‐Bickel syndrome (FBS) is a rare autosomal recessive disorder characterised by impaired glucose liver homeostasis and proximal renal tubular dysfunction. It is caused by pathogenic variants in SLC2A2 coding for the glucose transporter GLUT2. Main clinical features include hepatomegaly, fasting hypoglycaemia, postprandial hyperglycaemia, Fanconi‐type tubulopathy occasionally with rickets, and a severe growth disorder. While treatment for renal tubular dysfunction is well established, data regarding optimal nutritional therapy are scarce. Similarly, detailed clinical evaluation of treated FBS patients is lacking. These unmet needs were an incentive to conduct the present pilot study. We present clinical findings, laboratory parameters and molecular genetic data on 11 FBS patients with emphasis on clinical outcome under various nutritional interventions. At diagnosis, the patients' phenotypic severity could be classified into two categories: a first group with severe growth failure and rickets, and a second group with milder signs and symptoms. Three patients were diagnosed early and treated because of family history. All patients exhibited massive glucosuria at diagnosis and some in both groups had fasting hypoglycaemic episodes. Growth retardation improved drastically in all five patients treated by intensive nutritional intervention (nocturnal enteral nutrition) and uncooked cornstarch with final growth parameters in the normal range. The four severely affected patients who were treated with uncooked cornstarch alone did not catch up growth. All patients received electrolytes and l‐carnitine supplementation to compensate for the tubulopathy. This is one of the largest series of FBS on therapeutic management with evidence that nocturnal enteral nutrition rescues growth failure.